Hyangga – poetry in their native language - Aмирбековa, У. A. (Journal of Oriental Studies, 2017)
The article is devoted to ancient Korean poetry in the genre hyangga. It considers its relationship with folk customs and rituals, it notes the influence of shamanism and Buddhism in popular songwriting. The conclusion is that the poetic tradition of Korea originates in ancient hyangga.